Nanoscale Biophysics of the Cell - Ashrafuzzaman, Mohammad (Springer International Publishing, 2018)
Macroscopic cellular structures and functions are generally investigated using biological and biochemical approaches. But these methods are no longer adequate when one needs to penetrate deep into the small-scale structures and understand their functions. The cell is found to hold various physical structures, molecular machines, and processes that require physical and mathematical approaches to understand and indeed manipulate them. Disorders in general cellular compartments, perturbations in single molecular structures, drug distribution therein, and target specific drug-binding, etc. are mostly physical phenomena. This book will show how biophysics has revolutionized our way of addressing the science and technology of nanoscale structures of cells, and also describes the potential for manipulating the events that occur in them.